Preoperative cachexia index can predict the prognosis of extrahepatic biliary tract cancer after resection. (September 2022) - Hamura, Ryoga; Haruki, Koichiro; Shirai, Yoshihiro; Tanji, Yoshiaki; Taniai, Tomohiko; Okui, Norimitsu; Furukawa, Kenei; Shiozaki, Hironori; Onda, Shinji; Ikegami, Toru
Abstract: Introduction: Cachexia is associated with poor survival of patients with bile duct cancer. The cachexia index (CXI), which comprises skeletal muscle, inflammation, and nutritional status, has been proposed as a novel biomarker of cancer cachexia. In this study, we investigated the prognostic significance of the cachexia index after surgical resection of extrahepatic biliary tract cancer. Methods: Between January 2008 and December 2020, 124 patients underwent radical resection of extrahepatic biliary tract cancer. The skeletal muscle index (SMI) was calculated as the area of the psoas muscle at the third lumbar vertebra/(height) 2 . CXI was calculated using as: SMI × serum albumin level/neutrophil-to-lymphocyte ratio. We performed univariate and multivariate analyses of the relationships between clinicopathological variables and disease-free and overall survival. Results: The CXI-low group included 57 patients. CXI-low was associated with poor disease-free ( p  < 0.01) and overall survival ( p  < 0.01) after curative resection. Preoperative bile duct drainage ( p  = 0.01), poor tumor differentiation ( p  = 0.04), advanced Tumor-Nodes-Metastasis (TNM) stage (II or III) ( p  < 0.01), and CXI-low ( p  = 0.03) were independent and significant predictors of disease-free survival. Age > 70 years ( p  = 0.03), preoperative bile duct drainage ( p  < 0.01), poor tumor differentiation (p = 0.01), advanced TNM stage (II or III) ( p  = 0.03), and CXI-low ( p  = 0.04) were independent and significant predictors of overall survival. Conclusion: In extrahepatic biliary tract cancer, preoperative CXI-low was an independent and significant risk factor for recurrence and poor prognosis, suggesting that cancer cachexia may progress to tumor development and recurrence. Highlights: Cancer cachexia has been associated with poor survival in patients with biliary tract cancer. The cachexia index, which consists of skeletal muscle, inflammation, and nutritional status, may be useful in the assessment of cancer cachexia. The cachexia index can be a prognostic indicator in patients with extrahepatic biliary tract cancer.